2019
DOI: 10.1073/pnas.1818907116
|View full text |Cite
|
Sign up to set email alerts
|

Cell-autonomous FLT3L shedding via ADAM10 mediates conventional dendritic cell development in mouse spleen

Abstract: Conventional dendritic cells (cDCs) derive from bone marrow (BM) precursors that undergo cascades of developmental programs to terminally differentiate in peripheral tissues. Pre-cDC1s and pre-cDC2s commit in the BM to each differentiate into CD8α+/CD103+ cDC1s and CD11b+ cDC2s, respectively. Although both cDCs rely on the cytokine FLT3L during development, mechanisms that ensure cDC accessibility to FLT3L have yet to be elucidated. Here, we generated mice that lacked a disintegrin and metalloproteinase (ADAM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 42 publications
2
32
0
Order By: Relevance
“…Yet, the drastic reduction in NOTCH2dependent cDC1s and cDC2s in conditional ADAM10 knockout mice strongly suggests that ADAM10 is the essential NOTCH2 sheddase in DCs. In support of our findings, a role of dendritic cell ADAM10 in the differentiation of cDC2s and the generation of T H 2 responses was previously reported by us and others (53,54). Although off-target effects of the CD11c-driven Cre have been described (55,56), our mixed bone marrow experiments clearly confirmed the effects of ADAM10 to be cell-intrinsic.…”
Section: Discussionsupporting
confidence: 92%
“…Yet, the drastic reduction in NOTCH2dependent cDC1s and cDC2s in conditional ADAM10 knockout mice strongly suggests that ADAM10 is the essential NOTCH2 sheddase in DCs. In support of our findings, a role of dendritic cell ADAM10 in the differentiation of cDC2s and the generation of T H 2 responses was previously reported by us and others (53,54). Although off-target effects of the CD11c-driven Cre have been described (55,56), our mixed bone marrow experiments clearly confirmed the effects of ADAM10 to be cell-intrinsic.…”
Section: Discussionsupporting
confidence: 92%
“…[96, 104,105]. Consistent with the literature, Itgax was expressed in multiple macrophage populations (Figure 2A) at levels at least as high as in purified DC, and correlated only with Cd22, Cd274 (encoding PD-L1), Csf2rb, Csf2rb2, Slc15a3, Tmem132a and the transcription factor gene Prdm1 (Cluster145).…”
Section: Dendritic Cell Co-expression Clusterssupporting
confidence: 88%
“…The transcript encoding the ligand (Flt3l) was expressed constitutively to varying degrees in all of the MPS populations studied. Fujita et al [104] showed that FLT3L is cleaved from the cell surface of expressing cells by ADAM10. Conditional deletion of Adam10 using Itgax-cre led to reduced differentiation of cDC2.…”
Section: Dendritic Cell Co-expression Clustersmentioning
confidence: 99%
“…Despite evidence that it is expressed by many resident tissue macrophages (reviewed in [ 25 ]), CD11C (encoded by Itgax ) is still widely used as a surface marker in mouse DC purification. Ongoing studies of the impacts of conditional mutations using Itgax -cre continue to be interpreted solely in terms of DC specificity (for example, [ 121 , 129 , 130 ]). Consistent with the literature [ 25 ], Itgax was expressed in multiple macrophage populations other than DCs ( Fig 2A ) at levels at least as high as in DCs purified using CD11C as a marker and correlated only with Cd22 , Cd274 (encoding programmed cell death 1 ligand 1), Csf2rb , Csf2rb2 , solute carrier ( Slc ) 15a3 , Tmem132a , and the transcription factor gene Prdm1 (Cluster145).…”
Section: Resultsmentioning
confidence: 99%
“…The transcript encoding the FLT3 ligand ( Flt3l ) was expressed constitutively to varying degrees in all of the MPS populations studied. Fujita and colleagues [ 129 ] showed that FLT3L is cleaved from the cell surface of expressing cells by ADAM10. Conditional deletion of Adam10 using Itgax -cre led to reduced differentiation of cDC2s.…”
Section: Resultsmentioning
confidence: 99%